Assessing the Alignment of Pharmacotherapeutics Course Outcomes With Topic Outcomes - Vera, Numa (Am J Pharm Educ, 2019)
Objective. To determine the level of alignment between course and topic outcomes of a third- and fourth-year pharmacotherapy curriculum. Methods. Each topic taught in each course was categorized into subtopics and each subtopic had a set of learning outcomes. The learning outcomes for the courses and subtopics were matched to examine alignment. Cognitive levels were categorized using the Structure of the Observed Learning Outcome (SOLO) taxonomy of prestructural, unistructural, multistructural, relational, or extended abstract. The types of knowledge that the curriculum was intended to instill also were categorized as declarative or functioning. Results. There were eight explicit course outcomes for each course and 140 subtopic outcomes for course 1 and 136 for course 2. Wide variations in alignment between the courses and subtopic outcomes were found. Issues identified included the use of redundant verbs and insufficient alignment and balance of cognitive levels and types of knowledge embedded in each outcome. Conclusion. Alignment between the course and subtopic outcomes was not optimal. Using a constructive alignment analysis, learning outcome issues that need improvement for course alignment were identified. The methodology used here can be applied to other courses to promote effective curriculum design.